A Metric for Quantifying Product‐Level Circularity. (24th February 2017) - Linder, Marcus; Sarasini, Steven; van Loon, Patricia
Summary: Circularity metrics are useful for empirically assessing the effects of a circular economy in terms of profitability, job creation, and environmental impacts. At present, however, there is no standardized method for measuring the circularity of products. We start by reviewing existing product‐level metrics in terms of validity and reliability, taking note of theoretically justified principles for aggregating different types of material flows and cycles into a single value. We then argue that the economic value of product parts may constitute a useful basis for such aggregation; describe a set of principles for using economic value as a basis for measuring product circularity; and outline a metric that utilizes this approach. Our recommendation is to use the ratio of recirculated economic value to total product value as a circularity metric, using value chain costs as an estimator. In order to protect value chain actors' sensitive financial data and facilitate neutrality regarding outsourcing or insourcing, we suggest a means to calculate product‐level circularity based on sequential approximations of adding one product part and activity at a time. We conclude by suggesting potential avenues for further research, including ways in which the proposed metric can be used in wider assessments of the circular economy, and ways in which it may be further refined.